The Potential for the Application of the Emerging Market Z-score Model in the Case of Listed Banks in Ghana - Dramani Angsoyiri; Anthoinette Ativor (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
The primary goal of the research is how to put into operation the emerging market (EM) Z-score model in predicting corporate failure and to evaluate financial performance through the analysis of the annual audited report of four quoted banks in Ghana. More so this research introduces the Z-score model in this sector as a tool for possible diagnostic behind financial performance and deterioration. The method used in this research is primarily based on the EM Z-score model developed by Altman. The approach used in this research is in line with previous research that upholds the Z-score model with 80 percent prediction accuracy. These previous researchers confirm that it is a robust instrument that helps in predicting and assessing the overall performance of companies financially and possible distress of corporate organizations given that it consists of numerous ratios financially which can be utilized to predict business liquidation, financial distress, and corporate failure. The method set up in this research is to study the annual report of banks quoted on the Ghana Stock Market by computing their Altman emerging market Z-score ratio for three years that is from 2016 to 2019 and comparing it with 2019 which is the current year emerging market Z-score ratio to evaluate the whole performance of the banks financially as well as the possibility of liquidation of banks quoted on the Ghana Stock Market. The research establishes that banks in Ghana should work hard on enhancing the Z-score ratios which are dragging the emerging market Z-score down to better comprehend the earlier period performance and to realize their current situation in the sector; the Z-score can be adopted by banks in Ghana as an effective and efficient assessment approach towards the financing the possible long joint venture projects encompassing Small and Medium businesses enterprises. This model was adopted by banks in Ghana as an autonomous credit hazard examination approach to appraising the financial strength and competencies of potential projects. It was ascertained from this research that the Altman emerging market Z-score ratio model is an applicable model for measuring the performance of quoted banks in Ghana. Limitation including the Ghanaian banking sector is still considered to be a small size that may have negative consequences on the maximum result of the research. Future research should be conducted towards updating coefficient value associated with every ratio in the Altman emerging market Z-score ratio model as per the inputs from the banks in Ghana